2003
DOI: 10.1007/s11883-003-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled hypertension as a risk for coronary artery disease: Patient characteristics and the role of physician intervention

Abstract: Hypertension is the most widely treated cardiovascular risk factor, and there is clear evidence of the efficacy of treating systolic and diastolic blood pressure with existing antihypertensive agents in reducing stroke and cardiac disease. However, only about 25% of the US population has blood pressure controlled to at least 140 mm Hg systolic and 90 mm Hg diastolic. Hypertension control is a complex function of patient and physician behavior. Although poor hypertension control has historically been attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…However, the respective treatment goals were achieved in significantly fewer subjects in group A than in group B. Whether this finding was simply due to the difficulty of reducing SBP below a critical level, or whether it may also have been related to other causes, such as the attitude of investigators toward less intensive treatment in elderly patients (24) or the poor adherence of patients to treatment (4), remains to be elucidated. It is expected, however, that BP differences between the two groups will increase towards the end of the treatment phase.…”
Section: Discussionmentioning
confidence: 99%
“…However, the respective treatment goals were achieved in significantly fewer subjects in group A than in group B. Whether this finding was simply due to the difficulty of reducing SBP below a critical level, or whether it may also have been related to other causes, such as the attitude of investigators toward less intensive treatment in elderly patients (24) or the poor adherence of patients to treatment (4), remains to be elucidated. It is expected, however, that BP differences between the two groups will increase towards the end of the treatment phase.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is particularly burdensome among racial/ethnic minority groups and hypertension-related cardiovascular disease has been shown to be the greatest contributor to previously documented racial differences in mortality [5-12]. Although higher rates of hypertension control and a reduction in racial differences in outcomes from hypertension may be obtained by increasing providers' aggressiveness in intensifying therapy when indicated [2,12], several studies have demonstrated that providers often allow their patients to remain poorly controlled [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although higher rates of hypertension control and a reduction in racial differences in outcomes from hypertension may be obtained by increasing providers' aggressiveness in intensifying therapy when indicated [2,12], several studies have demonstrated that providers often allow their patients to remain poorly controlled [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated substantial problems in the quality of hypertension treatment and low rates of blood pressure control, as well as racial and socioeconomic disparities. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Hypertension is particularly burdensome among racial/ethnic minority groups 7-14 and hypertension-related cardiovascular disease has been shown to be the greatest contributor to racial differences in mortality. 12 Several reviews have emphasized the importance of designing pragmatic interventions to improve care and reduce disparities in outcomes of chronic diseases [15][16][17] ; one such intervention may be the use of computerized decision support (CDS).…”
mentioning
confidence: 99%